49 Reduced myocardial perfusion reserve in systolic heart failure a therapeutic target?. (June 2018) - Brown, Louise; Saunderson, Christopher; Onciul, Sebastian; Broadbent, David; Fent, Graham; Foley, James; Chew, Pei Gee; Garg, Pankaj; Xue, Hui; Dall'Armellina, Erica; Swoboda, Peter; Greenwood, John; et al.
Abstract : Background: Left ventricular systolic dysfunction (LVSD) is associated with reduced myocardial perfusion reserve (MPR) even in the absence of proven ischaemic heart disease and patients may have typical angina symptoms, despite the lack of obstructive coronary artery disease. The severity of MPR reduction has been suggested as a prognostic marker in both ischaemic and non-ischaemic cardiomyopathy. We hypothesised that reduction in MPR was associated with worsening symptomatology (NYHA class) and systolic dysfunction (ejection fraction, EF). Methods: 40 patients referred from cardiology clinics with LVSD of unknown cause underwent adenosine stress perfusion CMR (Siemens 3T). First pass stress and rest myocardial perfusion CMR data were acquired in three short axis slices with 0.05 mmol/kg intravenous Gadovist using a recently reported free-breathing motion corrected Method with in-line quantification of perfusion maps. For stress, adenosine was administered at 140 mcg/kg/min over 5 min. Segments showing regional perfusion defects or containing scar were excluded from further quantitative analysis. Myocardial blood flow (MBF) was calculated globally for the remaining left ventricle. Patients with no evidence of LVSD (EF-55%) were excluded from analysis. NYHA class was recorded at the time of CMR scan. EF was calculated from a short axis cine data set and classified as: mild (45%), moderate (3544%) and severe (34%) impairment. ANOVA with post hoc Bonferroni correction was used to compare means of the three groups. Results: Patients were grouped both by NYHA class and by EF severity, comparisons of these groups are shown in Table 1. No significant difference was seen between groups with respect to age, resting heart rate and resting MBF. MPR was associated with NYHA class (figure 1). A greater reduction in MPR was associated with a higher NYHA class and there was a significant decrease in MPR between asymptomatic patients and those with exercise limitation (Mean MPR 2.90±0.96, 2.05±0.61, 1.45±0.45 for classes I, II and III respectively, p<0.01). No significant difference was seen between NYHA II and III (2.05 vs 1.45, p=0.32) although a trend to decreasing MPR was observed. Myocardial perfusion reserve did not correlate with severity of LV dysfunction (figure 2). Conclusion: A reduction in MPR is associated with NYHA class in systolic heart failure, independent of ejection fraction. These findings suggest potential therapeutic targets for symptomatic improvement, including use of vasodilators, even in the absence of coronary disease.